A história e a memória a nos guiar no Rio de Janeiro: proposta para um guia de viagem - Guimarães, Carlos Eduardo Leal (2012)
This current essay tries to accomplish some reflections about the cultural tourism in the city of Rio de Janeiro, through the creation of a travel guide with themed routes based on the history of the city. This guide would present new forms to observe the urban landscape considering the main role played by the city in the Brazilian history as political and cultural capital. The major focus of the foreseen itineraries would be the nation’s republican phase from the end of the XIX century till the 1970’s. In this period, Rio has faced innumerable urban changes which would be also analyzed during a series of walking-tours described in the travel guide. Based on this approach, the paper analyzes the formulation possibilities for this touristic product through theoretical references about Collective Memory, Sites of Memory, Cultural Identity and Heritage Interpretation. Taking advantage from these concepts, the study explains this emerging style of cultural tourism as an incentive for local residents to become travellers in their own city, as citizen- tourists.